(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Hyperbaric oxygen (HBO) treatment is steadily increasing as a therapeutic modality for various types of diseases. Although good clinical outcomes were reported with HBO treatment for various diseases, the multisystemic effects of this modality are still unclear. This study aimed to investigate the renal effects of HBO experimentally. Materials and Methods. Fourteen New Zealand White rabbits were divided into 2 groups randomly as the control group and the study group. The study group received HBO treatment for 28 days (100% oxygen at 2.5 atmospheres for 90 minutes daily) and the control group was used to obtain normal renal tissue of the animal genus. After the intervention period, venous blood samples were obtained, and renal tissue samples were harvested for comparisons. Results. Normal histological morphology was determined with Masson trichrome staining and periodic acid-Schiff staining in the control group. Atrophic glomerular structures, vacuolated tubule cells, and degeneration were detected in the renal samples of the study group with Masson trichrome staining. Additionally, flattening was observed on the brush borders of the proximal tubules, and tubular dilatation was visualized with periodic acid-Schiff staining. The histopathologic disruption of renal morphology was verified with detection of significantly elevated kidney function laboratory biomarkers in the study group. Conclusions. Our findings suggests that HBO has adverse effects on renal glomerulus and proximal tubules. However, the functional effects of this alteration should be investigated with further studies.